Meningkatkan Kinerja Karyawan: (Studi Mengenai Partisipasi Kerja dan Motivasi Kerja Pada Karyawan Koperasi Kota Bengkulu) - Hariyadi, Rizky (Disclosure: Journal of Accounting and Finance, 2023)
The background to this research focuses on the importance of employee performance in facing the challenges of globalization and increasingly fierce business competition. Superior employee performance has a positive impact on achieving company goals, innovation and organizational competitiveness. The two main factors that play a role in improving employee performance are work participation, which involves employees in making decisions and contributing ideas, and work motivation, which encourages employees to achieve goals and give their best effort in Bengkulu City cooperatives. The aim of this study is to examine whether work participation and work motivation influence employee performance either partially or simultaneously. This research is associative research with a quantitative approach. This sampling technique uses non-probability sampling. The sample for this research was 48 members of Koperasi Kartika Kota Bengkulu. While the data analysis technique ini this research used multiple regression analysis. The results of this research are that work participation has a positive but not significant effect on employee performance, while work motivation has a significant positive effect on employee performance. Meanwhile, work participation and work motivation simultaneously have a positive but not significant effect.